2005
DOI: 10.1359/jbmr.041108
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Sensitive Sensory Neurons Contribute to the Maintenance of Trabecular Bone Integrity

Abstract: This investigation used capsaicin to selectively lesion unmyelinated sensory neurons in rats. Neuronal lesioning induced a loss of trabecular integrity, reduced bone mass and strength, and depleted neuropeptides in nerve and bone. These data suggest that capsaicin-sensitive sensory nerves contribute to trabecular bone integrity.Introduction: Familial dysautomia is an autosomal recessive disease in which patients suffer from unmyelinated sensory neuron loss, reduced BMD, and frequent fractures. It has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 72 publications
(126 reference statements)
8
123
2
3
Order By: Relevance
“…The results of macroscopic analysis showed no difference in body weight between animals with and without sciatic nerve injury, suggesting that skeletal unloading due to muscle inactivity of the hind limbs did not contribute to the loss of bone integrity demonstrated by histologic analysis. Similar results have been reported by Offley et al (2005) who evaluated the contribution of capsaicinsensitive sensory neurons to the maintenance of trabecular bone integrity. These authors also observed a loss of bone mineral density in the tibial and femoral metaphyses of rats 4 weeks after capsaicin treatment.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of macroscopic analysis showed no difference in body weight between animals with and without sciatic nerve injury, suggesting that skeletal unloading due to muscle inactivity of the hind limbs did not contribute to the loss of bone integrity demonstrated by histologic analysis. Similar results have been reported by Offley et al (2005) who evaluated the contribution of capsaicinsensitive sensory neurons to the maintenance of trabecular bone integrity. These authors also observed a loss of bone mineral density in the tibial and femoral metaphyses of rats 4 weeks after capsaicin treatment.…”
Section: Discussionsupporting
confidence: 87%
“…These results support the hypothesis that sensory neurons contribute to the maintenance of trabecular bone integrity, which can be explained by the fact that neuropeptides such as substance P and calcitonin gene-related peptide (CGRP) are synthesized by sensory neurons and released from peripheral nerve terminals. A reduction in the levels of these local neuropeptides in bone affects bone integrity (Maayan et al 2001;Offley et al).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF, CGRP and SP contents in the sciatic nerve were measured as we have previously described (Offley et al 2005). Briefly, nerve samples were minced in 1 ml of 3:1 ethanol/0.7M HCl and homogenized for 20 s. The homogenates were shaken for 2 h at 4°C and centrifuged at 3000g for 20 min at 4°C.…”
Section: Homogenization Procedures and Enzyme Immunoassay For Ngf Cgrmentioning
confidence: 99%
“…Starting with leptin at the turn of the century [13], the number of central mediators of bone metabolism has grown significantly and their roles now extended to controlling bone homeostasis rather than simply exerting a positive or negative effect on bone. Our understanding of neuronal control has extended from the sympathetic nervous system [14] to the parasympathetic and sensory nervous systems [15,16]. Abnormalities in the central nervous system such as vestibular dysfunction may also indirectly affect bone mass [17].…”
mentioning
confidence: 99%